2011
DOI: 10.1080/19368623.2011.536071
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of English Tourists Visiting Turkey Based on Attitudes Toward Internet Use in Vacation Decision Making

Abstract: The profiling of tourists according to their decision behavior is not new, but the popularity of the Internet and its increasing rolein tourist decisions is becoming an important area of research. This study aimed to profile English tourists visiting the Turkish Aegean summer resort of Kuşadası based on their attitudes toward Internet use in vacation decision making. Research data was collected from tourists in the hotels of Kuşadası. A total of 338 surveys were used in the analysis. The tourists' attitudes to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 29 publications
(73 reference statements)
0
6
0
Order By: Relevance
“…In line with this trend, since the late 1990s, many resort hotels in Turkey began offering all-inclusive packages (Barak, 2006). Consequently, Turkey has become an international player in the resort hotel industry for the last two decades (Duman and Tanrisevdi, 2011; Gunlu et al, 2010; Sanliöz Özgen and Kozak, 2015). According to the Association of Turkish Travel Agencies, Turkey ranked third in selling all-inclusive packages in Europe (TURSAB, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In line with this trend, since the late 1990s, many resort hotels in Turkey began offering all-inclusive packages (Barak, 2006). Consequently, Turkey has become an international player in the resort hotel industry for the last two decades (Duman and Tanrisevdi, 2011; Gunlu et al, 2010; Sanliöz Özgen and Kozak, 2015). According to the Association of Turkish Travel Agencies, Turkey ranked third in selling all-inclusive packages in Europe (TURSAB, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…When Internet booking became available for OPP its use increased and the use of the call center declined (B. Vanstaalduinen, personal communication, 2010). Duman and Tanrisevdi (2011) found that the tourists studied had high levels of involvement with Internet use in vacation decisions, suggesting higher levels of Internet use in destination choice and booking in recent years.…”
Section: Characteristics Of the Opp Booking Systemmentioning
confidence: 93%
“…The Switching Barrier Scale (Han et al, 2011) Internet Use in Vacation Decision Making Scale (Duman and Tanrisevdi, 2011) Visitor Engagement Scale (Taheri and Jafari, 2014) Tourists' Emotional Experiences (Hosany et al, 2015) Purchase Decision-Making Criteria Scale (Ozdipciner et al, 2010) 14 Shopping at Destinations and Trust Scale (Choi et al, 2016) Consumer Typology Scale (Gallarza et al, 2017) Customer Participation Scale (Chen and Raab, 2017) Host Sincerity Scale (Taheri et al, 2018) Functional Congruity Scale (Wang et al, 2018) 6 Human resources scales 17 Hospitality Emotional Labour Scale (Chu and Murmann, 2006) Antecedents of Employee Loyalty Scale (Chen and Wallace, 2011) Job Satisfaction Scale (Khalilzadeh et al, 2013) 2 Hospitality Industry Organizational Culture Scale (Bavik, 2016) Scale of Hospitableness (Tasci and Semrad, 2016) Cultural Competence for Tour Leaders (Tsaur and Thu, 2019) (continued ) Servicescape elements, both a marketing mix element (physical evidence) and a service quality dimension (tangibles), may influence tourism and hospitality customers' decisions and evaluations significantly (Bilgili et al, 2020). As discussed below, it may be recommended from a data collection perspective that the influence of servicescape elements on customers, as well as employees, may be measured by using scales developed by using psychophysiological tools.…”
Section: Scope Perspectivementioning
confidence: 99%